Influence of the α-relaxation on the high-velocity stretchability of isotactic polypropylene. (18th June 2020) - Eichelter, Johanna; Wilhelm, Harald; Eder, Andreas; Mautner, Andreas; Bismarck, Alexander
Abstract: The influence of the molecular weight ( M W ) of isotactic polypropylene (iPP) on the activation energy of the α-transition ( E A α ) and the stretching behaviour was investigated and correlations drawn. Mechanical relaxations in polyolefins are related to the mobility of polymer chains. The temperature of the α-transition in polyolefins increases with test frequency and draw ratio. Furthermore, the α-transition (i.e. intracrystalline chain dynamics) in polyolefins is related to thermally activated molecular motions, and thus a relationship between E A α, crystal growth, and plastic deformation exists. Stretched films and tapes of synthetic polymers are important in industrial packaging applications such as heavy duty BigBags or weaves. Many studies investigated either stretching or mechanical relaxations of semi-crystalline polymers, however, reports on direct correlations between E A α of polyolefins and their stretching behaviour are scarce. Furthermore, different DMTA-modes and sample preparation methods have not been compared and correlated yet. In this study, correlations between E A α of iPP-grades with different M W relevant for the entire processing range and their stretchability were investigated. Stretchability as well as mechanical properties and crystallinity of stretched tapes were highest for iPP-grades with a medium M W (346–360 kg/mol), while they were lower for low (218 kg/mol) and high M W (610 kg/mol), respectively. Ultimately, a linear relationship between E A α and stretchability was found for different iPP-grades for which a lower E A α resulted in higher stretchability, which correlated with higher crystallinities and mechanical properties of stretched tapes. Results obtained for iPP were also confirmed for low density (PE-LD) and high density (PE-HD) polyethylene. In addition, the impact of DMTA-mode (tension, torsion, and 3-point-bending) and sample preparation method (extruded tapes, compression moulded, and injection moulded specimen) for DMTA-measurements was evaluated. Graphical abstract: Image 1 Highlights: High-velocity stretchability and mechanical properties of polyolefins tapes can be concluded from the EA of the α-transition. Lowest EA and highest stretchability obtained for iPP with medium MW. Linear relationship between EA and stretchability for iPP-grades with different MW established. Increasing crystallinity and mechanical properties of iPP tapes with decreasing MW. Correlations between EA and stretchability confirmed for other polyolefins (PE-LD and PE-HD).